Rahasia Dan Hikmah Nabi Zakaria A.S Tidak Berbicara Selama Tiga Hari: Telaah Surah Ali ‘Imran Ayat 41 - Mohammad Fattah; Afifah Aulia Adelia; Moh. Fawaid (Dirosat : Journal of Islamic Studies, 2020)
Up to the present, the Qur'an still holds various implied secrets and still challenges scientists and all other opponents who still have doubts about the Qur'an to prove its truth. Muslims are required not to focus their point of view only on the miracles of the Qur'an itself, but also to focus more on the wisdom contained in it. As the story of the prophet Zakaria a.s in surah A<li ‘Imra>n verse 41 where Allah SWT gave a sign to him of his wife's pregnancy in the form of not being able to speak the prophet Zakaria a.s for three days. This certainly has great wisdom that can only be found with an in-depth study of the story. This study tried to uncover the secret and wisdom behind the inability of the prophet Zakaria a.s to speak for three days in the eyes of the famous mufassir namely Fakhr al-Din al-Razi in His tafsir Mafa>tih al-Ghaib, Ibn ‘Athiyyah in His tafsir al-Muharrar al-Waji>z and al-Alusi in His tafsir Ru>h al-Ma'a>ni. This research formulates that the secret and wisdom behind the inability of the prophet Zakaria to speak for three days as a sign that Allah SWT gave for the truth of his wife's pregnancy is that it is intended that he focus on dhikr to Allah SWT as a form of gratitude for the great blessings of the good news of his wife's pregnancy in their old age, as mentioned by the three mufassir figures above in the book of their Tafsir. As for Ibn 'Athiyyah in addition to agreeing with al-Razi and al-Alusi, he also added that it was a calamity (punishment from Allah SWT) because he doubted the news.